(untitled) (Foro de Educacion, 2024)
The postulates on education from Celestín Freinet, and his determination to provide to the Cooperative of Lay Education (CLE) of an international character, came out soon the French borders. Spain was not foreign to such influence and, very soon, the Freinet’s educational offer had a good reception, even though, in the first moment, it had scanty diffusion and minor application. The winds of pedagogic renovation, propitiated by the Spanish Second Republic, gave impulse and encouraged the application of the new educational technologies from France. Thus, the incipient Freinet’s Spanish movement was taking shape and, in a little time, this had a «battalion» of «sniper» teachers, who wanted to apply those ideas, a solid organization and a promising future truncated by the beginning of the civil war. This research is about the Spanish receipt from the Modern School, the advertising and diffusion of those ideas, the itinerary followed by the Spanish’s Freynet move- ment during it expansion and Franco’s government. Likewise, this paper presents a profile of the Freynet’s teachers movement in Spain, and a census of school notebooks realized through the school press, with expression of the locality of edition and of the teachers who stimulated the publication.